Empirical Investigation of Five-Factor Model of Personality - Fahrudin JS Pareke; Rina Suthia Hayu (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
The concept of Five-Factor Model (FFM) of Personality describes the basic dimension of human behavior, thinking, and emotions that related to the job. The FFM currently getting popular and reach more attention to from the scholars and practitioners as well, particularly in the area of human resource management. Therefore, the main goal of current research is to compile and to test the dimensions of FFM and its measure empirically. Eighty-four self report measures distributed to the 238 employees who work both for public and private organizations at the Northern Sumatera Island, Indonesia. The respondents are currently completing their graduate programs at the University of Bengkulu. Two-hundred-and-eighteen questionnaires completed and returned by respondents, and analyzed using Factor Analysis with Varimax Approach to extract them in to the several components. Based on the analyses, research confirmed the 5 dimensions for FFM, which is conscientiousness (18 items), extraversion-introversion (18 items), agreeableness (12 items), openness to experience (14 items), and emotional stability (12 items). The result strictly recommended that the use of FFP as a means of Human Resource Practices such as selection, promotion, training, and the like.Keywords: Agreeableness, Conscientiousness, Emotional Stability, Extraversion, Openness to Experiences, Personality